Development of Novel Formulation of Anesthetic from Rosewood (Aniba rosaeodora) for Anesthetizing Thai Red-Hybrid Tilapia (Oreochromis niloticus) - Ruenthoy, Natnicha; Achapisit, Nutthakarn; Maneepark, Montree; Praphairaksit, Nalena (Science Essence Journal, 2021)
Using an anesthetic in fish transportation and surgical procedure is an effective way to reduce stress and injuries before surgery and during transportation in fish. Currently, synthetic chemical such as MS-222 is widely used as a fish anesthetic. However, the residue can be found in fish and can harm the consumers. Therefore, natural remedies are of interest in substituting chemical anesthetic. In this study, we used rosewood essential oil (Aniba rosaeodora Ducke) as a fish anesthetic due to the property of linalool that has been shown to induce anesthesia. In addition, the essential oil was developed into the emulsion to increase the water solubility and effectiveness as a drug carrier in Thai red-hybrid tilapia (Oreochromis niloticus). The rosewood essential oil emulsion was prepared by the catastrophic phase inversion technique. The fish were immersed in an anesthetic solution with different concentrations to determine induction and recovery time. The results showed the best concentration of rosewood emulsion for fish transportation was 0.02 mL/L which can hold the fish at stage 1 anesthesia for 2 hours and the fish recovered after 3 minutes. The best concentration for stage 3 anesthesia to perform surgery was at 0.15 mL/L, the fish were anesthetized to stage 3 within 3 minutes and recovered within 5 minutes. Thus, rosewood essential oil emulsion can be used as an effective anesthetic in fish with good solubility.